Guppies Prefer to Follow Large (Robot) Leaders Irrespective of Own Size - Bierbach, David; Mönck, Hauke J.; Lukas, Juliane; Habedank, Marie; Romanczuk, Pawel; Landgraf, Tim; Krause, Jens (Frontiers in Bioengineering and Biotechnology, 2020)
Body size is often assumed to determine how successful an individual can lead others with larger individuals being better leaders than smaller ones. But even if larger individuals are more readily followed, body size often correlates with specific behavioral patterns and it is thus unclear whether larger individuals are more often followed than smaller ones because of their size or because they behave in a certain way. To control for behavioral differences among differentially-sized leaders, we used biomimetic robotic fish (Robofish) of different sizes. Live guppies (Poecilia reticulata) are known to interact with Robofish in a similar way as with live conspecifics. Consequently, Robofish may serve as a conspecific-like leader that provides standardized behaviors irrespective of its size. We asked whether larger Robofish leaders are preferentially followed and whether the preferences of followers depend on own body size or risk-taking behavior (‘boldness’). We found that live guppies followed larger Robofish leaders in closer proximity than smaller ones and this pattern was independent of the followers’ own body size as well as risk-taking behavior. Our study shows a ‘bigger is better’ pattern in leadership that is fully independent of behavioral differences among differentially-sized leaders, followers’ own size and risk-taking behavior.